Genetic Improvement of Chickpea through Induced Mutation - Samiullah Khan, M. Imran Kozgar (Journal of Phytology, 2009)
Following seed treatment by two mutagens (HZ and MMS), four chickpea mutant lines were evaluated to find out selection response in M3 generation. Estimates of variability for yield and yield components were recorded higher. In comparison with the control plants, nitrate reductase activity (NRA) in leaf tissues of all the mutant lines was increased. The early maturity mutant lines showed the highest seed protein content and NRA.